Dihydropyrimidine dehydrogenase deficiency as a cause of fatal 5-Fluorouracil toxicity - Shiraz S. Fidai; Aarti E. Sharma; Daniel N. Johnson; Jeremy P. Segal; Ricardo R. Lastra (University of São Paulo, 2018)
5-Fluorouracil (5-FU), in combination with other cytotoxic drugs, is commonly used to treat a variety of cancers. Dihydropyrimidine dehydrogenase (DPD) catalyzes the first catabolic step of the 5-FU degradation pathway, converting 80% of 5-FU to its inactive metabolite. Approximately 0.3% of the population demonstrate complete DPD deficiency, translating to extreme toxicity of 5-FU. Here we present a case of a patient who had a fatal outcome after treatment with 5-FU who was found to have an unknown DPD deficiency discovered at autopsy.